Trascendencia de la COVID-19 en el incremento de deserción escolar en Ecuador durante 2019 - 2022 - Ochoa Quezada, Edwin Manuel (2022)
The outbreak of the covid-19 pandemic posed a threat to the advancement of education due to negative impacts such as: the closure of all educational institutions and economic recession, caused by measures taken to minimize the impact of the pandemic. The closure of educational institutions caused a loss of learning and an increase in school dropout rates accompanied by a lack of economic resources, inequity, difficulty in accessing public education and disease. In the case of Ecuador during 2020, education showed an absenteeism rate of 27%, and the lack of technological resources, which through analysis during this period had an impact of 14%. The objective of this study is based on the need to determine the new causes that generated vulnerability in students in the presence of the covid-19 pandemic. For the development of this study, a quantitative analysis was used in conjunction with the econometric propensity score matching method that will allow us to determine the impact that the presence of covid-19 had on education, supported by the National Survey of Employment, Unemployment and Underemployment (ENEMDU, 2022). On the other hand, it was determined that the main causes of school dropout during the study period were: lack of economic resources, lack of interest in attending an educational center, pregnancy, illness and lack of technological resources. Consequently, a positive relationship was established between the income level of the heads of household and school attendance. The strengthening of the unemployment insurance system is recommended, which could be acquired through a financial institution or a trilateral format